2014
DOI: 10.2134/agronj13.0503
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Irrigation and Plant Density for Improved Cotton Yield and Fiber Quality

Abstract: An important limitation to cotton (Gossypium hirsutum L.) production in the Texas High Plains is water shortage. A 2‐yr study was conducted at two locations in Lubbock, TX, in 2007 and 2008 to determine the optimal irrigation and plant density for cotton production in the Texas High Plains based on yield and fiber quality. A field experiment was conducted by using a split plot design, with irrigation (0, 2.54 and 5.08 mm d−1) as the main plot, and plant density (75,300; 150,600; and 226,000 plants ha−1) as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
29
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 26 publications
10
29
2
Order By: Relevance
“…This was due to variations in growing season temperature and rainfall, which affected fiber maturation. Several studies reported a decrease in fiber micronaire as irrigation rate increased (Bauer and Frederick, 2005; Basal et al, 2009; Dagdelen et al, 2009; Feng et al, 2014).…”
Section: Results and Dissucionmentioning
confidence: 99%
“…This was due to variations in growing season temperature and rainfall, which affected fiber maturation. Several studies reported a decrease in fiber micronaire as irrigation rate increased (Bauer and Frederick, 2005; Basal et al, 2009; Dagdelen et al, 2009; Feng et al, 2014).…”
Section: Results and Dissucionmentioning
confidence: 99%
“…Higher crop yield with increased plant density has been reported in many field crops, including cowpea (Vigna unguiculata L.) (El Naim and Jabereldar 2010), cotton (Gossypium hirsutum L.) (Feng et al 2014), maize (Zea mays) (Amanullah et al 2009;Antonietta et al 2014), rapeseed (Brassica napus) (Wang et al 2015), and winter wheat (Triticum aestivium) (Dai et al 2014). In these crops, seed yield is usually associated with plant morphological and physiological traits, such as plant density.…”
Section: Discussionmentioning
confidence: 99%
“…More available water postflower may increase seed yield but may decrease the weight of individual seeds (Feng et al 2014). In the present study, precipitation varied among growing seasons (1 May-31 August) from an average of 213 ± 2.7 mm (dry) to 308 ± 2.8 mm (normal) to 418 ± 1.9 mm (wet).…”
Section: Maturity and Plant Densitymentioning
confidence: 99%
“…Cotton is a crop whose perennial nature results in a flexible growth habit, with a relatively flexible relationship between in-field plant density and yield [1]. This flexibility complicates stand assessments and replant decisions [3][4][5][6][7].…”
Section: Of 14mentioning
confidence: 99%
“…Variation from the desired populations and distribution of plants within a field can reduce yield as compared to a more uniform planting [1][2][3][4]. Understanding the resource demands of the crop (radiation, water, and nutrition), and planting in a manner that provides for those needs, is an essential part of modern agriculture.…”
Section: Introductionmentioning
confidence: 99%